Lateral jaw motion in fish expands the functional repertoire of vertebrates and underpins the success of a dominant herbivore lineage - Michalis Mihalitsis; Denise Yamhure-Ramirez; Maelan H. Beil; HoWan Chan; Nathan J. Cole; Ava Luenenborg; Isabella Paglione; Hallee Petri; Nicole C. Shum; Dylan K. Wainwright; Bryson Zheng; Peter C. Wainwright (Proceedings of the National Academy of Sciences, 2025)
The primary function of the vertebrate jaw is the dorsoventral movement that occurs during opening and closing. Yet, several lineages have evolved the ability to move their jaws laterally, enabling major innovations, like chewing. While lateral jaw motions are primarily known in tetrapods, here, we show that an ecologically dominant lineage of reef fishes (Zanclidae and Acanthuridae) has evolved the ability to laterally rotate their jaws during feeding. This unique function substantially expands both the kinematic versatility and known diversity of vertebrate jaw mechanisms, adding to the growing list of innovations that followed the origin of jaws. Within Acanthuridae, this increased kinematic versatility may allow for algal detachment with minimal movement of the rest of the body, facilitating rapid biting within the same microtopographic location, and thus, this lineage having the highest bite rates among biting reef fishes. This innovation may have thus helped create one of the most ecologically diverse and speciose herbivorous reef fish lineages. Our results highlight the ecological and evolutionary impact of lateral jaw rotation within vertebrates, and potentially how this novelty led to a significant change in coral reef trophodynamics.